Synergistic effects of 15-deoxy Δ(12,14)-prostaglandin J(2) on the anti-tumor activity of doxorubicin in renal cell carcinoma - Yamamoto, Yasuhiro (Biochem Biophys Rep, 2016)
An endogenous anticancer agent, 15-deoxy -Δ(12,14)-prostaglandin J(2) (15d-PGJ(2)) induces apoptosis in the chemoresistant renal cell carcinoma (RCC). Peroxisome proliferator-activated receptor-γ (PPARγ) is a nuclear receptor for 15d-PGJ(2), and mediates the cytotoxicity of 15d-PGJ(2) in many cancerous cells. However, 15d-PGJ(2) induces apoptosis independently of PPARγ in human RCC cell line such as Caki-2. In the present study, we found that 15d-PGJ(2) ameliorated the chemoresistance to one of anthracycline antibiotics, doxorubicin, in Caki-2 cells. Doxorubicin alone exhibited weak cytotoxicity at the concentrations effective for other cancer cells such as Hela cells. In addition, it did not activate caspase 3. However, the cytotoxicity of doxorubicin was increased remarkably and accompanied with the caspase- 3 activation in the presence of 15d-PGJ(2). Doxorubicin alone damaged plasma membrane, and the combined application of 15d-PGJ(2) with doxorubicin increased the membrane permeability slightly. PPARγ was involved in neither the anti-tumor activity nor the synergistic effect of 15d-PGJ(2). 15d-PGJ(2) induces apoptosis in Caki-2 cells via suppressing the phosphoinositide 3-kinase (PI3K)-Akt pathway. The effect of PI3K inhibitor on the cytotoxicity of doxorubicin was additive, but not synergistic. Although the PI3K inhibitor mimicked the cytotoxicity of 15d-PGJ(2), it might not be involved in the synergism between 15d-PGJ(2) and doxorubicin. In conclusion, 15d-PGJ(2) enhanced the chemosensitivity of doxorubicin via the pathway independent of PPARγ and PI3K.